DEVELOPMENT AND VALIDATION OF A MATH MANIPULATIVES INSTRUCTIONAL MATERIAL FOR GRADE 5 - Sacramed, Olivia (Studies in Technology and Education, 2026)
This study aimed to develop and validate Mathematics manipulative instructional materials for Grade 5 learners of Atok Elementary School and determine their effectiveness in improving learners’ academic performance in Mathematics. Specifically, it sought to identify the Grade 5 learning competencies that require manipulative tools, develop appropriate instructional materials, evaluate the materials through expert validation, and determine the significant difference between the learners’ pre-test and post-test scores after using the developed materials. The study employed a descriptive-evaluative research design using a single-group pre-test and post-test approach. The respondents consisted of 14 Grade 5 learners and 3 expert validators from the school quality assurance team. The developed materials were evaluated using the Department of Education standard evaluation tool, while learners’ academic performance was measured through pre-test and post-test assessments. Mean, standard deviation, and paired t-test were used in analyzing the data. Findings revealed that the developed manipulative instructional materials were rated Very Satisfactory by the validators. The learners’ mean scores increased from 11.50 in the pre-test to 21.64 in the post-test, showing a significant improvement in performance. The study concluded that manipulative instructional materials effectively enhance learners’ understanding of mathematical concepts and improve academic achievement, highlighting their importance in strengthening Mathematics instruction among elementary learners.